La gestion des déchets post-catastrophe à Port-au-Prince : entre relégation et proximité - Roxana Popescu; Mathieu Durand; Robert d’Ercole (EchoGéo)
Waste-disaster production is often considerate less urgent or less important than access to health or water. However, it may be central in recovery and reconstruction process of the affected area. It reduces negatives effects (pollution, canal obstruction, interrupted communications...) while participating in economic revitalization of this area (waste recycling, stimulating economic sectors...).In this context, the article presents results of research carried out in the metropolitan area of Port-au-Prince and one of its districts, Tabarre, following the January 12, 2010 earthquake. The aim is to analyze spatial dimension of waste post-disaster management. This analysis permit to understand the destination of 94% of the 10 million m3 of earthquake-waste, that have not been sent to the official landfills and recycling center. It allows understanding the spatial logics waste management implemented by national and international authorities, such as civil society and informal sector. It correspond to relegation waste logical threw sacrificed spaces. This removal takes place at several scales, taking into account use landing and proximity between the waste fields and waste disposal sites. Existing logic of spatial household waste and construction waste management are exacerbating after the disaster. The findings made in Port-au-Prince agree with international feedback about disasters. These advocate, as possible, anticipated management of post-disaster waste, especially where disasters are frequent, as in Haiti, including planning of landfills and temporary intermediate places for transit and sorting waste.